Diagnosis and Treatment of Fournier Gangrene in Secondary Hospital; A Report of Two Cases - David Reiner Hutajulu; Hafizh Fanani Rizkyansyah (Journal Research of Social Science, Economics, and Management, 2021)
Fournier Gangrene (FG) is a specific form of necrotizing fasciitis that localized on genital and perianal, although it is rare but it is progressively fast and potentially fatal. The incidence of FG is 1.6 cases per 100,000 males, with a case fatality rate of 7.5%. Proper diagnosis and management are very important to avoid serious complications. Early debridement, broad-spectrum antibiotics and immediate supportive therapy, can reduce mortality. The objective is reporting two cases of FG who were admitted to a secondary hospital and what is the best management based on our setting. The method is qualitative observational study. The material collected through direct interview and from medical record. The best management for our setting was rapid diagnosis and followed by prompt debridement.